Determinants of Stunting in Pre-School-Aged Children in Ujung Bulu Subdistrict - Asnidar Asnidar; Haerani Haerani; Nour Sriyanah; Andi Suswani (Global Health Science Group, 2022)
Stunting is one of the main nutritional problems in children in Indonesia. Stunting becomes a serious problem because it is associated with the quality of human resources in the future. Stunted toddlers will experience a level of intelligence that is not optimal, making children more susceptible to disease and in the future will be at risk of decreasing productivity levels. The purpose of this study was to determine the factors related to the incidence of stunting in pre-school age children. This type of research is observational analytics with a case-control design. The subjects of the study studied were toddlers who experienced and did not experience stunting. The sample of this study was children in PAUD schools and kindergartens in Ujung Bulu District, a total of 43 people consisting of 23 stunted children as cases and 20 children who were not stunted as controls. The results showed that the results of the statistical factor test of ANC services (p = 0.001), breastfeeding (p = 0.000) and consumption of Fe tablets (p = 0.012) were related to stunting events. Meanwhile, the factor of the child's immunization history (p = 0.091) is not related to the incidence of stunting. It is recommended to pregnant women to pay more attention to ANC visiting services, breastfeeding and child immunization because it plays a very important role in stunting events.